Single-UV-photon 2-D imaging with multi-GEM detectors - Maia, J. M. (2007)
The main goal being the construction of large-area, low-cost position-sensitive micropattern gaseous photomultipliers (GPMs) based on gas electron multipliers (GEM) cascades, we have studied the single-photon imaging capabilities of a 4-GEM GPM with a reflective CsI-photocathode deposited on the top surface of the 1st GEM. The charge readout was performed with a simple/economic Wedge and Strip (W&S) readout electrode, using pulses induced through a resistive electrode. We have demonstrated the feasibility of single-photon imaging GPM with sub-millimeter resolution; single-photon spatial resolutions as small as ~150Â [mu]m (FWHM), i.e. ~65Â [mu]m (RMS), were measured in Ar/5%CH4 gas mixture at atmospheric pressure.